2016
DOI: 10.19082/2679
|View full text |Cite
|
Sign up to set email alerts
|

Pattern and Outcome of Acute Disseminated Encephalomyelitis (ADEM) in Children: Experience in a Tertiary Center, Upper Egypt

Abstract: IntroductionAcute disseminated encephalomyelitis (ADEM) is an immune mediated disease of the brain. Although it occurs in all ages, most reported cases are in children and adolescents. The aims of this study were to study the clinical pattern and outcome of ADEM in children in a tertiary center in Upper Egypt and to determine the effect of combined use of steroids and IVIg on outcome.MethodsThis observational study was carried out from January 2014 through December 2014 in the Pediatric Department of Sohag Uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Disturbed consciousness, motor impairment and seizure are frequently found in many series including ours. 12 Early studies of ADEM reported mortality rates up to 20% with a high incidence of neurological sequele in survivors. [13][14][15][16] In our study mortality was nil.…”
Section: Discussionmentioning
confidence: 99%
“…Disturbed consciousness, motor impairment and seizure are frequently found in many series including ours. 12 Early studies of ADEM reported mortality rates up to 20% with a high incidence of neurological sequele in survivors. [13][14][15][16] In our study mortality was nil.…”
Section: Discussionmentioning
confidence: 99%
“…Even though most children show excellent clinical recovery and normalization of MRI findings, neurological sequelae have been observed [ 59 ], specifically in children before 5 years of age [ 60 ]. The most common sequelae include cognitive impairment, epilepsy, visual and motor deficits (weakness, spasticity, ataxia), and impairment in speech.…”
Section: Treatmentmentioning
confidence: 99%
“…Intravenous immunoglobulin could be used as a second-line treatment, particularly in fulminant acute disseminated encephalomyelitis cases who did not respond to corticosteroids. 8 Abdrabou et al 9 reported that patients who received steroids on the first day and intravenous immunoglobulin during the first week of symptom onset had a better outcome. If there is a concern of infection, then intravenous immunoglobulin could be used as an alternative to corticosteroids.…”
Section: Discussionmentioning
confidence: 99%